DIAGNOSIS AND THERAPEUTIC MANAGEMENT OF COMPLICATED MIDDLE EAR CHOLESTEATOMA. A NARRATIVE REVIEW - Marius Cristian Mârțu; Alexandru Stingheriu; Oana Aștefanei; Iustin Iațentiuc; Ioana Mârțu; Oana Bitere-Popa (Romanian Journal of Oral Rehabilitation)
Cholesteatoma of the middle ear is a chronic inflammatory condition characterized by the presence, formation, or migration of epithelial cells into the mucosal region of the middle ear. This results in the progressive development of a matrix-like sac filled with keratinized debris arranged in concentric layers. Clinically, it typically presents with symptoms such as hearing loss, a sensation of ear fullness, and occasionally otorrhea (auricular suppuration).